The CXCL12/CXCR4 chemokine ligand/receptor axis in cardiovascular disease - Döring, Yvonne; Pawig, Lukas; Weber, Christian; Noels, Heidi (Frontiers in Physiology, 2014)
The chemokine receptor CXCR4 and its ligand CXCL12 play an important homeostatic function by mediating the homing of progenitor cells in the bone marrow and regulating their mobilization into peripheral tissues upon injury or stress. Although the CXCL12/CXCR4 interaction has long been regarded as a monogamous relation, the identification of the pro-inflammatory chemokine MIF as an important second ligand for CXCR4, and of CXCR7 as an alternative receptor for CXCL12, has undermined this interpretation and has considerably complicated the understanding of CXCL12/CXCR4 signaling and associated biological functions. This review aims to provide insight into the current concept of the CXCL12/CXCR4 axis in myocardial infarction and its underlying pathologies such as atherosclerosis and injury-induced vascular restenosis. It will discuss main findings from in vitro studies, animal experiments and large-scale genome-wide association studies. The importance of the CXCL12/CXCR4 axis in progenitor cell homing and mobilization will be addressed, as will be the function of CXCR4 in different cell types involved in atherosclerosis. Finally, a potential translation of current knowledge on CXCR4 into future therapeutical application will be discussed.